2014
DOI: 10.1186/1472-6831-14-104
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, pattern and perceptions of cleft lip and cleft palate among children born in two hospitals in Kisoro District, Uganda

Abstract: BackgroundCleft lip with or without cleft palate is one of the most common congenital anomalies that affect the oro-facial region. The aim of the study was to determine the period prevalence, pattern and perceptions of cleft lip and cleft palate in children born between 2005 and 2010 in two hospitals in Kisoro District, Uganda.MethodsThe study involved a retrospective review of medical records of mothers who delivered live babies between January 2005 and December 2010 in Kisoro Hospital and St. Francis Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 28 publications
(46 reference statements)
5
20
1
1
Order By: Relevance
“…In our current study, most of the patients with orofacial clefts (55.6%) were males. This is similar to the Ugandan study (9) and the study conducted in Tanzania by Manyama et al (18). The study done by Martelli Junior et al (19) in a Brazilian population reported similar findings.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our current study, most of the patients with orofacial clefts (55.6%) were males. This is similar to the Ugandan study (9) and the study conducted in Tanzania by Manyama et al (18). The study done by Martelli Junior et al (19) in a Brazilian population reported similar findings.…”
Section: Discussionsupporting
confidence: 91%
“…However, these rates are similar in the sense that they are lower than other population and consistent with what has been reported for clefts in Africa. Kesande et al (2014) in a retrospective analysis of births at two Ugandan hospitals found a prevalence of 0.77/1000 live births (9). This also is higher than our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present findings revealed a significantly lower birthweight of infants with CPO as compared to the control groups. The same trend has been described in populations in Iran, Taiwan and Uganda …”
Section: Discussionsupporting
confidence: 83%
“…This finding is different from a study where parents did not look upon their child as handicapped but as having a congenital defect or "flaw" [3]. But in another study in Uganda, about 91.7% of the medical staff reported that these children were not accepted in their communities [8]. In this current study, 10 of the mothers admitted to the fact that they were so embarrassed by their babies' condition that they would not bring their babies out least someone sees them and gossips about them.…”
Section: Reactions From Familycontrasting
confidence: 59%